Conceptualizing, Implementing, and Monitoring a Structural Health Promotion Intervention in an Organizational Setting. Issue 3 (May 2013) - Saunders, Ruth P.; Evans, Alexandra E.; Kenison, Kelli; Workman, Lauren; Dowda, Marsha; Chu, Yong H.
This article presents a framework for developing and carrying out an implementation monitoring plan of a complex structural intervention in an organizational setting and describes seven steps for analyzing and reporting results for fidelity and completeness of implementation. This process is illustrated using the Environmental Interventions in Children's Homes (ENRICH) Wellness Project. ENRICH aimed to promote physical activity and healthful nutrition behaviors among children residing in children's group homes by working collaboratively with organizational staff. A comprehensive implementation monitoring plan was developed based on the particulars of the setting, context, and the program framework and used multiple data sources, criteria for evidence of implementation, and data triangulation to examine evidence for organizational implementation. Eleven of 17 organizations (65%) met the criteria for nutrition implementation whereas 9 of 17 (53%) met the criteria for physical activity implementation. Implementation data can be used descriptively, as described here, and may also be used in future outcome analyses to better understand project outcomes. The framework and evaluation approach are applicable to complex interventions in other organizational settings.